THE EDUCATIONAL PERSPECTIVE ON CONSTRUCTION OF STUDY HABIT IN THE FAMILY - Nurliana Nurliana; Miftah Ulya (EDU SCIENCES JOURNAL, 2023)
Learning activities are mental activities psychologically to change different behavior between before and after learning. Through learning one can understand many things. However, some students who do not yet understand and develop their potential require intensive guidance. Many learning problems can come from educators and students, such as different understanding abilities, concentration, steady state, enthusiasm for learning. Parents need to format children’s learning, so that the learning process changes behavior in a better direction and understands learning material towards a brilliant future generation. The research objective is to educate parents in a family learning environment to improve children’s learning styles through study habit. The theme raised was “Construction of Study habit from an Educational Perspective in the Family”. Study habit is a new breakthrough in education in formatting time and behavior. Interesting discussion, important for students to understand. The research method is through literature study using triangulation through data selection, data presentation, drawing conclusions, analysis through content analysis. Study habit in learning several stages: First, setting the timer. Second, setting the place. Third, material arrangement. Fourth, realizing the principle of lifelong learning as motivation. Fifth, filter activity. From an educational point of view, the family is fully responsible for formatting study habit in the family as a determinant of the child’s future education.